Halal Product Acceptance towards Intrapreneur Development - Intan Shaferi; Alisa Tri Nawarini; Rio Dhani Laksana (Journal of International Islamic Business Studies, 2024)
The acceptance of halal product is common in Indonesia. Dominated by the Muslim people, Indonesia become one of the larger countries that provide halal product. Situation relatively getting interesting when the halal product not only become one product to be consumed, but also how the intrapreneur involved in it. Intrapreneur needs to know the potential consumen and product. The research study about the acceptance halal product towards the intrapreneur development. This study conducted in Central Java Indonesia, with survey respondents. The result shows that the acceptance halal product has effect to intrapreneur development.